Integrasi Sistem Informasi Geografis (SIG) dan Metode Geofisika Induced Polarization (Studi Kasus pada Eksplorasi Mineral Mangan di Kabupaten Kampar Provinsi Riau) - , Erwin Anshari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research investigat the integration of geophysical data induced polarization method data in to geographic information system (GIS) with study manganese deposit exploration in Kampar Regency Riau Province. Induced Polarization method is difficult method to be integrated in GIS because the result of data processing produced subsurface raster vertically (pseudosection). Potency of manganese deposit in research area found in metasediment rock as phyllite and quartsite. The result of field observation interpretation found manganese shaped vein indicated as result from hydrothermal process. Integration process in this research including building geodatabase, analysis of geophysics data, and integrated data visualization. Building geodatabase classified base on data types, they are geophysics and geology data. Geodatabase produced later exported to.xml format till produce data model can be used another user. Analysis process including transformation from pseudosection datum point till produced new data as merge datum point from all line to spatial analysis. Exploring data showing that data produced not distributed normally, till need to normalize process. This matter based the reality that geophysical data is continuous data. Result of spatial analysis produced surface map to resistivity and chargeability value. Deliniation of anomaly as geophysics data transformation to geological data become basic of reclassification process. This stage base on raster value on surface map in borehole 1 and 2 are 2000 â¦m of resistivity and 30 msec of chargeability as range of manganese value. This result later conducted multiple map analysis (overlay) with Boolean operator of reclassification result value, and produced manganese potential area. Manganese potential area observed in borelhole 2 dan 3 shaped irregularly and layering. All process in integration and analyst is that has long step and modeling with model builder. From this model builder will give easiness to anatother user to apply this method.